Prevalence and associated factors of multi-drug resistant bacteria among different clinical specimens at wad Medani, Sudan: a four-year, cross-sectional study - Yousif B. Hamadalneel; Safa F. Eltoum; Zainab M. Almustafa; Wageeda S. Mustafa; Fatima O. Abdelsalam; Yousif M. Yousif; Asgad A. Alsdeeg; Marwa F. Alamin (Scientific Reports)
Abstract Multi-drug resistant organisms (MDROs) are a global health concern. Therefore, the aim of the study is to evaluate the prevalence of MDROs and associated factors among different clinical specimens. This was a retrospective cross-sectional study, conducted between January 2020 to October 2023 using recorded laboratory data of culture and drug sensitivity from the Pathology Center for Diagnosis and Research, University of Gezira, Wad Medani City, Sudan. Among the 1766 investigated clinical samples, 1255 (71.1%) were from female. The overall MDROs prevalence was 694 (39.3%). Blood samples 45(52.3%) and wound swabs 191(41.2%) had the most MDROs. Staphylococcus aureus (S. aureus) and Proteus spp. 42(75%) had the highest MDR among the gram-positive bacteria (GPB) and the gram-negative bacteria (GNB) respectively. A significant association was observed between cerebrospinal fluid (CSF) and urine samples with the presence of MDROs. This study revealed a moderate prevalence of MDROs. Which is more prevalent in blood samples, wound swabs and in GNB. S. aureus and Proteus spp. had the greatest MDR among the GPB, and GNB, respectively. CSF and urine samples were associated with the presence of MDROs. Implementing these findings enables the development of strategies to prevent AMR in Sudan and other comparable low-resource environments.